Faktor Domestik Yang Memengaruhi Kebijakan Luar Negeri Iran Terhadap Arab Saudi Pascaeksekusi Mati Nimr Al-Nimr - Bajri, Hilal Kholid; Akim, Akim (Jurnal ICMES, 2021)
This article explains the factors that influenced Iran's foreign policy towards Saudi Arabia after Nimr Al Nimr execution in 2016. Nimr Al Nimr is a well-respected Shia cleric in the Middle East. As the country with the largest Shia population globally, Iran condemned Saudi Arabia's actions so that relations between the two countries deteriorated, even leading to the severance of diplomatic relations. The research question posed is what the domestic factors that influence the policy are? This article is based on qualitative research by interviewing several Middle Eastern experts and collecting data from documents and mass media. In analyzing the data, the writers used the theory from Mintz and DeRouen regarding three domestic factors that influence a country's foreign policy, namely economic interests, the role of public opinion, and the electoral cycle. The research finds that the foreign policy taken by Iran after the execution of Nimr Al Nimr is closely related to economic interests, especially related to the implementation of the pilgrimage; in line with the opinion of the Iranian people who highly respect Nimr Al Nimr; and consideration of the electoral cycle, where the policies taken by Rouhani affected his victory in the 2017 elections.